Two or Three on the Bed? Jerome’s Interpretation of Isaiah 28:20 Reflecting Jewish Traditions - Kato, Teppei (2024)
A given translation of the Bible may appear mistranslated because it privileges a particular interpretation. This feature of exegetical particularity makes it extremely difficult to identify mistranslations of the Bible. For example, two versions in the Latin translation of Isa 28:20 inform Jerome’s apparent mistranslation: one with two people sleeping on the bed and the other with three. This example may appear a “mistranslation” by Jerome. However, through this translation, we can glimpse the Jewish tradition that informs its reading.
„Das Bett ist so schmal, dass einer von beiden herausfallen muss, und die kurze Decke kann nicht beide bedecken“ (Jes 28,20, Vg). Der hebräische Text geht davon aus, dass nur eine Person im Bett liegt, aber Hieronymus' Übersetzung unterstellt, dass ein Paar in einem Bett schläft, das zu schmal für es ist. Die Vorstellung des Paares lässt sich als Echo des jüdischen Midrasch verstehen – eines Midrasch, der sogar von drei Personen in dem einen Bett weiß.
Keywords: Götzendienst; haggadische Interpretation; jüdische Tradition; Übersetzungsfehler; 20; Jes 28